Educación ambiental para la conservación de abejas del género Melipona en el barrio Chiguango, parroquia Guayquichuma, cantón Catamayo, provincia de Loja - Castillo Paladines, Elsa Cecivel (2024)
In Ecuador, in recent years the development of socio-environmental studies has increased, where environmental education for bee conservation is analyzed, considering the environmental conditions from the perspective of rural communities. Therefore, it is essential to promote strategies to address the change in culture in communities to promote the conservation of species and the environment. These strategies must be motivated by socio- environmental awareness in the community, promoting the development of public policies. This research focuses on the analysis of the social, economic and environmental importance of raising bees of the genus Melipona from a conservation and economic approach. For the development of this research study, a general objective was proposed called “Contribute to community awareness for the conservation of bees of the Melipona genus in the Chiguango neighborhood of the Guayquichuma parish, Catamayo canton, province of Loja”; To meet this objective, two specific objectives were set, which are: (i). Evaluate the management and identify threats of breeding bees of the Melipona genus in the Chiguango neighborhood, Guayquichuma parish; (ii). Implement environmental education actions for the management and conservation of bees of the Melipona genus in the Chiguango neighborhood of the Guayquichuma parish. The results of the study indicate that people do not properly manage these species, which is related to the lack of training on the subject; ignorance in many cases leads to poor management of these bees, causing the degradation of this species. species. This is why environmental education as a participation strategy can mitigate the threats faced by bees of this genus, promoting an environmental culture based on conservation and sustainable production, through the use of technical Meliponaries developed during the training. to the community.